An update: emerging drugs to treat squamous cell carcinomas of the head and neck. (2nd October 2018) - Lee, Yoon Se; Johnson, Daniel E.; Grandis, Jennifer R.
ABSTRACT: Introduction : Subsequent to the 2006 FDA approval of cetuximab, a variety of molecular targeting agents have been evaluated in head and neck squamous cell carcinoma (HNSCC). The treatment outcomes of recurrent and/or metastatic (R/M) HNSCC, in particular, remain dismal. The 2016 FDA approval of PD-1 immune checkpoint inhibitors has expanded the treatment options for R/M HNSCC and highlights the potential for immune-based therapies. Areas covered : We will review the clinical application of EGFR-targeted agents, alone and in combination with other drugs. Molecular targeting agents directed against the IL6/PI3K/STAT3 signaling pathway will be covered. In addition, evaluation of immune checkpoint inhibitors in HNSCC, along with ongoing combination trials incorporating these agents, will be discussed. The expanded indications of emerging drugs and the potential clinical benefit of new drugs and treatment combinations will be summarized. Expert opinion : In recent years, there has been a major shift toward immunotherapy-based approaches for the treatment of HNSCC, leading to significant improvements in outcomes for a subset of patients. Leveraging the increased understanding of the genetic alterations that characterize individual HNSCC tumors will facilitate precision medicine approaches using targeted agents, immunotherapies, as well as standard chemotherapy and radiation.